Characterization of the environmental controls of a plastic production company of the municipality of Caçador-SC, Brazil - Campos, Roger Francisco Ferreira de; Borga, Tiago; García, Santiago Sánchez (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Many production processes have a high level of emission of environmental aspects and impacts, in order to seek the minimization of these environmental mitigators, the environmental license that employs the environmental controls of the companies was developed. The main objective of this paper is to analyze the characterization of the environmental controls of a company producing plastic pro-ducts in the municipality of Caçador/SC. For the development of the study, the controls established in the Environmental Operating License (EOL) were analyzed to carry out in situ and documentary characterization of environmental controls. Through the study it is possible to describe that the company is in compliance with environmental issues, since the company seeks to minimize the impacts generated. Thus, it can be concluded that the characterization of environmental controls is a method that helps to minimize environ-mental impacts, where it presents the positive and negative points of the interaction of the productive process with the environment.